Epstein-Barr virus nuclear antigen-2 detection and typing in immunocompromised children correlated with lymphoproliferative disorder biopsy findings - Mendes,Thiago Marques (2008)
Epstein-Barr virus (EBV), the causative agent of infectious mononucleosis, plays a significant role as a cofactor in the process of tumorigenesis, and has consistently been associated with a variety of malignancies especially in immunocompromised patients. Forty-four children and adolescents (21 liver transplant patients, 7 heart transplant, 5 AIDS, 3 autoimmune hepatitis, 2 nephritic syndromes, 2 medullar aplasia, 2 primary immunodeficiency disorder patients, 1 thrombocytopenic purpura and 1 systemic lupus erythematosus) presenting with chronic active EBV infection (VCA-IgM persistently positive; VCA-IgG > 20 AU/mL and positive IgG _ EBNA) had peripheral blood samples obtained during clinically characterized EBV reactivation episodes. DNA samples were amplified in order to detect and type EBV on the basis of the EBNA-2 sequence (EBNA2 protein is essential for EBV-driven immortalization of B lymphocytes). Although we have found a predominance of type 1 EBNA-2 virus (33/44; 75%), 10 patients (22.73%) carried type 2 EBNA-2, and one liver transplant patient (2.27%) a mixture of the two types, the higher proportion of type 2 EBV, as well as the finding of one patient bearing the two types is in agreement with other reports held on lymphoproliferative disorder (LPD) patients, which analyzed tumor biopsies. We conclude that EBNA-2 detection and typing can be performed in peripheral blood samples, and the high prevalence of type 2 in our casuistic indicates that this population is actually at risk of developing LPD, and should be monitored.